Comunicação publicitária e consumo da arte contemporânea: análise das lógicas de produção da publicidade da Bienal de Arte de São Paulo, de 2000 a 2010 - Casarotti, Marcio Geraldo (2013)
Would contemporary art be a product to be contemplated for consumption the same manner that other products and services are? Would its advertisement discourses and broadcasting follow the same strategies as production? Should they have the same information expectations, reverberations and articulation, understanding and meaning? This dissertation starts with perceptions of a differentiation between two territories that, although culturally intertwined as it advances throughout history, require a deeper epistemological proximity in contemporary time. Products and services offer tangible and intangible benefits in a functional, pragmatic and assertive universe. They are propelled for consumption by means of advertisement with less risks of incomprehension or mercantile inefficacy. On the other hand, contemporary art offers a much more open experience in terms of sense and meaning. Works of art, many times are adverse to an instantaneous understanding that labels them and freezes their cosmos of significance. Art, many times, works shaking language dimensions and discourses, the premises and basis of society development, logics and moralities. This research focuses its efforts on investigating the logics of production and advertisement strategies for consumption of contemporary art. In this sense, it focuses on the interaction between contemporary art and the global society of information and consumption, envisioning the understanding of its expression vectors, and how the advertisement speech has been used to communicate for the consumption of art nowadays. This will be discussed by an analyses of the integrated communication of advertisement for the Sao Paulo Biennal of Art in the editions of 2000 and 2010 and other contextual references, and also making reference to the French line of Discourse Analyses, enriched with the theoretical contribution of Rocha (2010) and Carrascoza (2007), among others.